Assessment of androgen receptor signaling inhibitors therapy in metastatic hormone-sensitive prostate cancer - Jukapun Yoodee; Chiraphon Detma; Onuma Lappanawan; Worachaya Pengthina (Faculty of Pharmacy, Mahidol University, 2022)
Androgen receptor signaling inhibitor (ARSI) therapy plays an important role in treating advanced prostate cancer. However, in Thailand, the efficacy and safety data of ARSI therapy remain limited. This study aimed to assess the efficacy and safety of ARSI therapy to treat patients with metastatic castration na?ve prostate cancer. We collected data from electronic medical records based on disease progression and any reported adverse events. The primary outcome was progression-free survival (PFS) after initiating ARSI therapy. Secondary outcome was PFS according to abiraterone and enzalutamide, risk factors associated with PFS of ARSI therapy and adverse events. A total of 49 eligible patients were enrolled having received ARSI therapy (abiraterone or enzalutamide) to treat metastatic prostate cancer. The median time to follow-up was 17 months (interquartile range, 12-31). PFS among patients treated with ARSI therapy was 22 months (95% confidence interval [CI], 17-33), PFS among patients with abiraterone and enzalutamide was 21 and 23 months, respectively (hazard ratio [HR], 0.48; 95% CI, 0.17-1.41, P=0.185). Patients with Eastern Cooperative Group status 1-2 exhibited significantly decreased risk of disease progression (HR, 0.44; 95% CI, 0.20-0.96, P=0.038). The common adverse events included hypertension and fluid retention and edema. In conclusion, abiraterone and enzalutamide showed a trend to improve PFS among patients with metastatic castration naive prostate cancer. Adverse events were rarely reported, and patients were able to tolerate treatment.